Human development in the economic institution in achieving sustainable development - keltouma, Boufatah (Journal of Social Sciences (COES&RJ-JSS), 2018)
The aim of this study is to show the impact of human development in the economic institution on sustainable development, where the modern economy based on the employment of knowledge will only be the development of capital Training and composition of the modern economic institution will not continue and will not be imposed only by creative persons with specialized knowledge adapted to the organizational climate characterized by gravity and through it and in the framework of the modern politicized style, the administration in this institution to make maximum use of each individual in order to achieve efficient performance For human resources management and for WHO as a whole within the framework of sustainable development.